New product development : smart money box / Nurul Atisyah Amran, Nur Fatini Nadziri @ Ismail and Mohammad Amir Suhairi Zuhairy - Amran, Nurul Atisyah; Nadziri @ Ismail, Nur Fatini; Zuhairy, Mohammad Amir Suhairi (2018)
The team will be developing a smart money box, a device that can split money according to their value of note or coin. This device is made from several complex machineries to scan the money, split the money according to the value and display the amount of the total money saved. The idea was mainly generated from internet and some surveys states that a device to split money according to their value is convenient to count the total money saved in money box. As this product is affordable and light, it is convenient for families to purchase and safely keep inside the house with children. A survey about the product concept among 21 students supports that this product is marketable and convenient for families with kids. The idea will be tested by 10 families with 3 children and will be tested at the market after the product is ready.